The father of the age of steel - Rumold, Ferdinand John (My University, 1898)
Introduction: The true inventor, like the poet, is “born, not made.” The subject of this thesis did not acquire the inventive ingenuity which characterized him their life. It was an inherited faculty. Sir Henry Bessemer’ father was a Frenchman who was employed in the mints of France about the time that Robespierre became dictator of the country, and was transferred from the mint to take charge of the public bakery that distributed bread to the mobs which thronged the street.
Citation: Rumold, Ferdinand John. The father of the age of steel. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: France; Inventor; Steel; Theses; Manuscripts (documents)